Analysis of Competency-Based Curriculum Development in Fresh Graduate Training Programs at HPI Agro - Sahala Antoni Purba; Laura Lahindah (Return : Study of Management, Economic and Bussines, 2024)
The competency-based curriculum is a critical component in designing effective training programs, particularly for industries requiring highly specialized skills, such as oil palm plantations. This study evaluates the competency-based curriculum development process for the fresh graduate training program at HPI Agro, focusing on its effectiveness in aligning training objectives with industry demands. Using a qualitative research approach, the study collected data through interviews, observations, and documentation analysis. The findings reveal several gaps in the current curriculum, including insufficient emphasis on technical skill mastery, lack of continuous evaluation during training, and limited integration of soft skills development. The proposed improvements include redesigning the curriculum to address these gaps, incorporating advanced training methodologies, and strengthening the mentoring system to enhance practical application. By refining the training program, HPI Agro can produce highly competent and competitive human resources, ensuring workforce readiness and organizational sustainability. This research contributes to the broader discourse on competency-based training and highlights the need for dynamic and context-specific curriculum development to meet evolving industry needs.